Capital market integration in South Asia : realizing the SAARC opportunity - Aiyer, Sourajit (Elsevier Asian studies series., 2017)
Capital market integration in South Asia: realizing the SAARC Opportunity discusses the potential capital market products/activities which can create closer inter-linkage of the South Asian capital markets and help local/global investors benefit from this economic opportunity. While some ideas may be implementable now; others have future promise as the regional markets further mature. The book demonstrates both retail and institutional investor interest in this combined high-growth region by offering scope for yield, diversification and risk mitigation, maximized upside from multiple growth markets, minimized downside through low-correlation constituents, and more. The book's core theme addresses the challenges towards deepening the awareness and acceptability of regional economies. Only when this happens will the asset flows increase into the regional market products, providing scale-up that will aid viability for these products. Presents unconventional ideas for converting SAARC's unique opportunities into ideas for capital markets Includes socioeconomic issues as a part of the discussion.